Kreativität und Teilhabe in der Stadt: Initiativen zwischen Kunst und Politik in Salzburg - Huber, Laila Lucie (transcript, 2017)
Thinking on the possibilities of the living environment of the city – this volume examines creativity and imagination as driving forces of urban participation, in the interplay between reality and utopia.